Biological Effects of Cardiac Magnetic Resonance on Human Blood Cells. (September 2015) - Lancellotti, Patrizio; Nchimi, Alain; Delierneux, Céline; Hego, Alexandre; Gosset, Christian; Gothot, André; Jean-Flory Tshibanda, Luaba; Oury, Cécile
<x xml:space="preserve">Abstract</x> Background— Cardiac magnetic resonance (CMR) is increasingly used for the diagnosis and management of cardiac diseases. Recent studies have reported immediate post-CMR DNA double-strand breaks in T lymphocytes. We sought to evaluate CMR-induced DNA damage in lymphocytes, alterations of blood cells, and their temporal persistence. Methods and Results— In 20 prospectively enrolled healthy men (31.4±7.9 years), blood was drawn before and after (1–2 hours, 2 days, 1 month, and 1 year) unenhanced 1.5T CMR. Blood cell counts, cell death, and activation status of lymphocytes, monocytes, neutrophils, and platelets were evaluated. The first 2-hour post-CMR were characterized by a small increase of lymphocyte B and neutrophil counts and a transient drop of total lymphocytes because of a decrease in natural killer cells. Among blood cells, only neutrophils and monocytes displayed slight and transient activation. DNA double-strand breaks in lymphocytes were quantified through flow cytometric analysis of H2AX phosphorylation (γ-H2AX). γ-H2AX intensity in T lymphocytes did not change early after CMR but increased significantly at day 2 ⩽1 month before returning to baseline levels of 1-year post-CMR. Conclusions— Unenhanced CMR is associated with minor but significant immediate blood cell alterations or activations figuring inflammatory response, as well as DNA damage in T lymphocytes observed from day 2 until the first month but disappearing at 1-year follow-up. Although further studies are required to definitely state whether CMR can be used safely, our findings already call for caution when it comes to repeat this examination within a month.